EKSPLORASI METAGENOMIK DARI SERANGGA BLACK SOLDIER FLY (Hermetia illucens) PENDEGRADASI SAMPAH ORGANIK DALAM UPAYA BIOREMEDIASI LINGKUNGAN - irwanto; Maman Rumanta; Rony Marsyal Kunda (Jurnal Penelitian Pendidikan IPA, 2025)
The Black Soldier Fly (BSF) (Hermetia illucens Linnaeus, 1758) has long been recognized as an organism used in organic waste processing through bioconversion methods. H. illucens is known to digest organic materials into nutrient sources utilized for biomass formation with the assistance of decomposer microbiota. However, research on the structure and composition of its microbiota remains limited. This study aims to identify microbiota and their structural composition in both the larval and adult fly phases, based on organic waste feeding in tropical regions. Additionally, it seeks to provide recommendations for relevant stakeholders in identifying potential environmental bioremediation agents. The research method employed is a survey study with quantitative sample analysis. The amplification process in this study uses primers from the (V1-V9) regions of the 16S rRNA gene. Data analysis is conducted using the QIIME (Quantitative Insights into Microbial Ecology) method, utilizing high-throughput sequencing community data with QIIME2 software version 3.5.3. Microbiota from the families Lactobacillaceae and Morganellaceae have been identified as dominant in larvae, while Staphylococcaceae and Bacillaceae dominate in adult flies. Morganella morganii, Herbaspirillum piri, Dysgonomonas capnocytophagoides, and Clostridium intestinale are potential candidates for organic waste bioremediation from BSF larvae. Meanwhile, Sphingobacterium wenxiniae, Lachnoclostridium phytofermentans, Mammaliicoccus sciuri, and Corticicoccus populi are bioremediation candidates from BSF flies. The genera Enterococcus, Morganella, and Dysgonomonas are found in both temperate and tropical climate regions. However, Providencia, Klebsiella, Scrofimicrobium, and Actinomyces, which are found in the gut of BSF larvae in temperate regions, are absent in BSF larvae from tropical Indonesia. Conversely, Limosilactobacillus, Entomomonas, Lachnoclostridium, and Clostridium are not found in the gut of BSF larvae in temperate regions.